2022
DOI: 10.1111/ajd.13910
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hidradenitis suppurativa on quality of life is worse than inflammatory bowel disease and myocardial infarction

Abstract: Quality of life is severely impacted by Hidradenitis Suppurativa. This crosssectional survey based study highlights that the impact of Hidradenitis Suppurativa on quality of life measured by the World Health Organisation Quality of Life (WHOQOL-BREF) survey is worse than published data for atopic dermatitis and other acute and chronic medical conditions including myocardial infarction and inflammatory bowel disease. K E Y W O R D Sabsenteeism and presenteeism, DLQI, hidradenitis suppurativa, HiSQOL, quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Interestingly, patients with HS have similar results in the mental dimension of the 36-Item Short Form Questionnaire (SF-36) as patients with diagnosed depression [42]. Similarly, Mortimore et al [43] showed that HS impacts QoL more profoundly than atopic dermatitis, myocardial infarction, or inflammatory bowel disease [43]. The influence of HS on patients’ psychological health is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with HS have similar results in the mental dimension of the 36-Item Short Form Questionnaire (SF-36) as patients with diagnosed depression [42]. Similarly, Mortimore et al [43] showed that HS impacts QoL more profoundly than atopic dermatitis, myocardial infarction, or inflammatory bowel disease [43]. The influence of HS on patients’ psychological health is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HS are more likely to experience psychiatric comorbidities and other medical conditions such as inflammatory bowel disease [33,34]. HS has been shown to have a greater impact on quality of life scores than major adverse cardiac events, lower limb amputation, hepatitis C, inflammatory bowel disease, eczema, acne, and psoriasis [35,36]. Increasing disease burden, unemployment, lower educational attainment, female sex, and increasing age are associated with decreased quality of life in HS [37,38].…”
Section: Discussionmentioning
confidence: 99%